Repair of the left ventricular wall pseudoaneurysm following myocardial infarction (simple modified dor technique). Issue 2 (2020) - Maleki, Mahmood Hosseinzadeh; Azdaki, Nahid; Rezvani, Mohammad Reza; Motlaq, Alireza Rahmani
No abstract available